Barriers, drivers and decision-making process for industrial energy efficiency: A broad study among manufacturing small and medium-sized enterprises. (15th January 2016) - Trianni, Andrea; Cagno, Enrico; Farné, Stefano
Highlights: Barriers and drivers vary along the decision-making process of EEM adoption. Economic barriers, awareness and behavioural are most critical. Beside economic drivers, major relevance of regulatory and vocational training. Importance of stakeholders providing technical support. Barriers and drivers are different according to several firm characteristics. Abstract: Energy efficiency has been recognized as a primary means to increase the competitiveness of the industrial sector, and in particular for small and medium-sized enterprises (SMEs), in which energy efficiency measures (EEMs) are scarcely implemented. For this reason, future policies should carefully address such issue. Hence, it is really crucial to have a precise and punctual knowledge of the barriers to be tackled in the decision-making process of adopting an EEM and the drivers to be promoted. This study discussed the findings from a broad investigation within 222 manufacturing SMEs located in a Northern Italy region. Beside economic issues particularly affecting SMEs, awareness and behavioural issues emerge as critical, affecting the very first steps of the decision-making process, related to the punctual identification and evaluation of plausible EEMs. The support from manufacturers, technology suppliers, installers and ESCOs supporting SMEs through vocational training drivers (e.g. technical support) is really important to tackle such issues. More generally, beside financial institutions, the supply chain of technologies is recognized as particularly useful for supporting enterprises in the adoption of EEMs. Additionally, having previously conducted energy audit and implemented EEMs are critical factors able to highlight non-economic barriers and drivers. Therefore, the promotion of EEMs will necessarily imply a further effort in pointing out the so-called non-energy benefits (NEBs) from the implementation of EEMs. Finally, our study reveals that smaller and non-energy intensive emerge as most critical and therefore deserve greater attention from policy-makers.